Effect of storage on beta-carotene content in Mango var. Chokanan puree - Johar, Mohd Hafizan; Azlan, Azrina; Ismail, Amin (Global Science Books, 2008)
This study was aimed to determine the effect of storage on the content of â-carotene in mango puree. Mango (Mangifera indica L.) from Chokanan variety was selected for this study. The â-carotene content at 0, 3, 6 and 24 days of storage were 4.74 ± 0.29 mg/100 g puree, 3.78 ± 0.21 mg/100 g puree, 3.42 ± 0.11 mg/100 g puree and 2.84 ± 0.55 mg/100 g puree respectively. â-Carotene content of mango puree was significantly different (P < 0.05) at different storage times. However, post-hoc test showed that the â-carotene content was significantly different (P < 0.05) between day 0 and day 24 of storage times. Storage at 5 C for more than 3 days reduced 20% of â-carotene content in mango puree. Prolong storage time of the puree for more than 24 days had reduced about 40% of â-carotene content in mango puree. The study indicated that â-carotene content in mango puree was significantly lost after 24 days of storage.